Organic, Inorganic and Hybrid Solar Cells: Principles and Practice - Lin Ch.-F. Ching-Fuh; Su W-F. Wei-Fang; Wu Ch.-I. Chih-I; Cheng I-Ch. I-Chun (Hoboken, John Wiley & Sons, Inc., 2012)
What will it take to transform solar energy from an important alternative source to a truly competitive and, perhaps, dominant one? Lower cost and longer life. Organic, Inorganic, and Hybrid Solar Cells: Principles and Practice provides in-depth information on the three types of existing solar cells, giving readers a good foundation for evaluating the technologies with the most potential for competing with energy from fossil fuels.Featuring a Foreword written by Nobel Peace Prize co-winner Dr. Woodrow W. Clark, this timely and comprehensive guide: